(untitled) (Research, Society and Development, 2020)
The present research had as main objective to verify the presence of the health theme in BNCC. The study is a documentary analysis of fragments of the text related to the health theme and keywords related to it. The analysis took place in two stages: first, the word “health” was verified, then the words healthy, healthy, well-being, quality of life, prevention and medical treatment were verified. As a result, from an overview of BNCC, the theme was found with greater concentration in texts related to Elementary Education, mainly in the curricular components of Science and Physical Education. It is noticed that the health perspective addressed in the science component is extremely biological and focused on reducing the risks to the disease. Regarding Physical Education, the adopted health perspective refers to aesthetics and body care, without taking into account the concern with environmental and social issues that may interfere with the population’s health. It is considered the need for schools to discuss and increase their curricula on this topic, as well as it is important that universities and sponsors promote actions that give special attention to the production of material and / or didactic sequences that can be implemented in the school. basic education, as well as supporting teachers.